1 Clinical Efficacy and Serum Inflammatory Factor Level (serum IFCs, bone Gla protein (BGP), and bone turnover markers β-collagen degradation product (β-CTX), and procollagen type 1 N-terminal propeptide (P1NP) )Changes of Zoledronic Acid and Denosumab in T: serum IFCs, bone Gla protein (BGP), and bone turnover markers β-collagen degradation product (β-CTX), and procollagen type 1 N-terminal propeptide (P1NP) ) - Ma, Jun (Journal of Medical Biochemistry, 2025)
Introduction: postmenopausal osteoporosis (PMOP) is a common bone disorder. Zoledronic acid and denosumab are widely utilized in the treatment of osteoporosis. This work aimed to explore the clinical effects and changes in serum inflammatory cytokine (IFC) levels of zoledronic acid and denosumab in the therapy of PMOP.Materials and Methods: eighty PMOP patients who visited our hospital from March 2021 to March 2024 were recruited and rolled into a control group (CG, n=40) and a treatment group (TG, n=40). CG received zoledronic acid plus traditional treatment, while TG received zoledronic acid plus denosumab plus traditional treatment. Clinical symptom improvement and changes in bone mineral density (BMD) were recorded and compared between the two groups. Changes in serum IFC levels were measured.Results: relative to CG, patients in TG showed greatly increased BMD (P<0.05), and markedly decreased levels of serum IFCs, bone Gla protein (BGP), and bone turnover markers β-collagen degradation product (β-CTX), and procollagen type 1 N-terminal propeptide (P1NP) (P<0.05). Additionally, the incidence of adverse reactions was drastically lower (P<0.05) in TG, and the total effective rate of clinical treatment was notably higher (P<0.05).Conclusion: zoledronic acid combined with denosumab demonstrates good clinical efficacy in PMOP patients, improving clinical symptoms and promoting increased BMD. Furthermore, this combined treatment regimen can reduce serum IFC levels, possibly promoting the treatment of osteoporosis by suppressing inflammatory responses.